2002
DOI: 10.1111/j.1751-0813.2002.tb11030.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of suburban Western Australians to proposed cat control legislation

Abstract: Cat legislation that avoids or educates about the contentious issue of cat-free zones should receive solid community support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 4 publications
6
70
0
Order By: Relevance
“…Australian cat-owners also show strong agreement with provisions to identify or register cats, although actual compliance may be lower. Grayson et al (2002) reported that 93% of female cat-owners and 82% of male catowners surveyed in Perth, Western Australia agreed that they would licence their cat with the local council if it became compulsory. Similarly, Murray et al (1999) found that 96.3% of residents on Magnetic Island off the Queensland coast were in favour of identifying and registering cats, although this figure includes non-owner responses as well.…”
Section: Attitudes and Practices Of Cat Ownersmentioning
confidence: 99%
See 1 more Smart Citation
“…Australian cat-owners also show strong agreement with provisions to identify or register cats, although actual compliance may be lower. Grayson et al (2002) reported that 93% of female cat-owners and 82% of male catowners surveyed in Perth, Western Australia agreed that they would licence their cat with the local council if it became compulsory. Similarly, Murray et al (1999) found that 96.3% of residents on Magnetic Island off the Queensland coast were in favour of identifying and registering cats, although this figure includes non-owner responses as well.…”
Section: Attitudes and Practices Of Cat Ownersmentioning
confidence: 99%
“…In Western Australia, Grayson et al (2002) found that 86% of cat owners agreed that cats in nature reserves were detrimental to wildlife, but only 50% of cat owners agreed that cat predation was a significant factor for suburban wildlife. Grayson et al (2002) also sought opinions on the proposition that local councils should have the power to prohibit cat ownership in new subdivisions. Cat-owners registered only 17% agreement.…”
Section: Attitudes and Practices Of Cat Ownersmentioning
confidence: 99%
“…Exclusion zones where residents are not pennitted to own a cat are one measure that might be considered to create buffer zones around sensitive wildUfe habitat. While they are accepted in some new subdivisions (Buttriss 2001), surveys of community opinion suggest that they attract at best luke~warm support in established suburbs (Grayson et al 2002, Lilith et aL 2006. Therefore successful implementation requires a detailed knowledge of the roaming habits of pet cats so that any buffer zone adopted is both adequate for wildlife protection and also of minimum size to reduce disruption to owners (sec Das 1993, Barratt 1997band Meek 2003 for relevant Austtalian studies andBradshaw 1992 andKays andDe Wan 2004 for relevant international studies).…”
Section: Introductionmentioning
confidence: 99%
“…Some research has begun (see Table 1), including investigating the use and perception of cat collars (cat owners preferred to use microchips for identification purposes; Harrod et al 2016), to the acceptability of unowned-cat control (respondents who owned cats perceived non-lethal control of unowned cats to be more acceptable than lethal control methods, when compared with non-owners; Farnworth et al 2011). A survey designed to better understand the attitudes of Western Australians towards cat-control legislation (Grayson et al 2002) has been adapted for use in other countries, including New Zealand. Results have indicated that most of New Zealand respondents agreed that pet cats in nature reserves are harmful to wildlife.…”
Section: Social Studiesmentioning
confidence: 99%